2000
DOI: 10.1056/nejm200004203421604
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acromegaly with the Growth Hormone–Receptor Antagonist Pegvisomant

Abstract: On the basis of these preliminary results, treatment of patients who have acromegaly with a growth hormone-receptor antagonist results in a reduction in serum IGF-I concentrations and in clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
543
6
34

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 792 publications
(618 citation statements)
references
References 24 publications
23
543
6
34
Order By: Relevance
“…The effectiveness of pegvisomant was almost similar to that in previous overseas clinical trials [12,13], in which serum IGF-I percentage change from baseline at 12 week by pegvisomant 20 mg daily was −62.5%, and IGF-I normalization was observed in 97% (87/90 subjects) for 12 months or more. However, the efficacy in normalizing IGF-I in a global safety surveillance study, ACROSTUDY, has been reported to be as low as 63.2% after 5 years of treatment [14] possibly due to inadequate dose adjustment.…”
Section: Discussionsupporting
confidence: 63%
“…The effectiveness of pegvisomant was almost similar to that in previous overseas clinical trials [12,13], in which serum IGF-I percentage change from baseline at 12 week by pegvisomant 20 mg daily was −62.5%, and IGF-I normalization was observed in 97% (87/90 subjects) for 12 months or more. However, the efficacy in normalizing IGF-I in a global safety surveillance study, ACROSTUDY, has been reported to be as low as 63.2% after 5 years of treatment [14] possibly due to inadequate dose adjustment.…”
Section: Discussionsupporting
confidence: 63%
“…Our results are closer to the data reported in the initial clinical trials with pegvisomant monotherapy and those from series of other tertiary centers than to the data reported in the last update of the Acrostudy (20)(21)(22)31,32). One of the possible reasons for a lower control rate in the Acrostudy is the clinical inertia (22).…”
Section: Discussioncontrasting
confidence: 46%
“…It can be used in monotherapy or in combination therapy with SA, in this case with greater efficacy. Normalization of IGF-I levels was achieved in more than 90% of the patients in the initial clinical trials and in 63.2% of the patients in the last update report of the Acrostudy (20)(21)(22). Therefore, it is the most effective drug in controlling IGF-I levels in acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Man denke hier z.B. an das oben beschriebene plazentare GH oder aber an den GHRezeptorantagonisten Pegvisomant [29] , der zur Behandlung der Akromegalie eingesetzt wird, aufgrund der hohen strukturellen Homologie zum Wildtyp-GH aber in vielen Assays interferiert.…”
Section: Wachstumshormon (Growth Hormone Gh)unclassified